A Pikes Peak partnership : the Penroses and the Tutts - Noel, Thomas J. (Thomas Jacob) (University Press of Colorado, 2000)
In A Pikes Peak Partnership, historians Tom Noel and Cathleen Norman tell the incredible tale of the two families who transformed Colorado Springs and its environs into a tourist haven. By building the Broadmoor Hotel and other important facilities to attract travelers, Spencer Penrose, who once proclaimed that "any man who works after lunch is a fool," made the Pikes Peak region a pleasure seeker's paradise.